Green Transformational Leadership in Improving Green Work Behaviour of Employee, with Green Organizational Citizenship Behaviour as Mediation - Harisinta, Tony (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
It is important to raise awareness about environmentally-friendly behaviour in organizations, especially organizations in government offices, which has begun expanding research related to green staff behavior. The aim of this study is to test green organizational citizenship behavior (GOCB) in mediating the influence between Green Transformation Leadership (GTL) and Employee Green Behavior (EGB). By using the survey method on 163 respondents who were willing to fill in the survey. By using the upsilon (v) statistical value test method to see the power of mediation influence in this model. The research findings explain that GOCB strongly mediates the relationship between Green Transformational Leadership (GTL) and Green Work Behavior (GWB) of employees.